Light‐Liquid Selective Filter‐Mounted Nanowire‐Networked Polyurethane Fiber for an Ultraviolet Sensor. Issue 19 (27th August 2019) - Lim, Taekyung; Jung, Sang‐Mi; Kang, Youngsoo; Ju, Sanghyun
Abstract: Fiber‐sensor‐based real‐time monitoring of the degree of exposure of the human body to ultraviolet (UV) rays is one of the technologies in the field of smart healthcare‐based wearable devices. With the development of wearable UV sensors, it is essential to build technologies with stable durability and excellent sensing capabilities for continuous movement and with water, sweat, and external contaminants. In this study, a fiber sensor is investigated that can stably detect UV intensity even when exposed to liquids such as water. The device consists of SnO2 nanowires, which are sensitive to UV intensity, arranged on a polyurethane (PU) fiber in a random network pattern, with the aim to minimize the amount of current change caused by various tensile and compressive stresses encountered by the wearable sensor. To prevent the distortion of the measured current that may occur in the semiconductor sensing channel as a result of external water exposure, a (1 H, 1 H, 2 H, 2 H ‐heptadecafluorodec‐1‐yl) phosphonic acid (HDF‐PA)‐coated Al2 O3 nanoparticles (NPs) with a UV transmittance of 77% are coated on the networked SnO2 nanowire channel. The SnO2 nanowire‐networked PU fiber covered with the HDF‐PA coated Al2 O3 NPs is confirmed to be sensitive only to UV, without reacting to external water under various bending conditions. Abstract : The tin oxide (SnO2 ) nanowire‐networked polyurethane fiber covered with a (1 H, 1 H, 2 H, 2 H ‐heptadecafluorodec‐1‐yl) phosphonic acid‐coated aluminum oxide nanoparticles can stably detect ultraviolet intensity even when exposed to liquids. The device consists of SnO2 nanowires, arranged on a polyurethane fiber, with the aim to minimize the amount of current change caused by various tensile and compressive stresses encountered by the wearable sensor.